Huma Betang: Identitas Moral Kultural Suku Dayak Ngaju Kalimantan Tengah - Apandie, Chris; Ar, Endang Danial (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
Nowadays local and national cultures are gradually left behind. Cultural artifacts—while having beyond-physical meaning, even moral and cultural identities—are no longer maintained neither have philosophical attraction. Exploration of philosophical values ​​in huma betang can be a step to revitalize culture in order to strengthen Indonesians’ cultural moral identity. Huma Betang is commonly known as